Semiconductor thermionics for next generation solar cells: photon enhanced or pure thermionic? - Ehsanur Rahman (Nature Portfolio, 2021)
A semiconductor thermionic device, which utilises thermally excited electrons, is considered as an alternative in solar conversion technology, yet its working mechanism is not clear. Here, the authors reveal that whether such a device operates in the photon enhanced or purely thermionic mode, greatly depends on the material properties and device physics.